Multiple cryptic species with divergent substrate affinities in the Serpula himantioides species complex - Carlsen, Tor (2011)
Serpula himantioides is a widespread saprotrophic morphospecies mainly colonising coniferous wood in nature, but it appears frequently in buildings as well. From an earlier study, it is known that at least three divergent lineages occur within the S. himantioides species complex. In this study, a broader sample of S. himantioides isolates has been analysed by multi-locus sequencing, including new isolates from Asia, North and South America. Altogether five phylogenetical species (PS1-5) were detected, all recognised across independent gene phylogenies. A new southern South American phylogenetic species (PS1) was found, representing an early diverging lineage within the S. himantioides species complex. The two closely related PS2 and PS3 lineages included isolates from North America only, and PS4 was also dominated by North American isolates. Most of the investigated isolates (76. %) clustered into PS5, a lineage that has been found on most continents, including North America. Overall, little phylogeographical structure was found in PS5, indicating frequent and recent long-distance dispersal events within this widespread lineage. Our analyses indicate that South and North America are the centres of divergence for the S. himantioides species complex. Some of the lineages seem adapted to various substrates, but PS5 is able to decay a wide array of angiosperms and gymnosperms, which may have facilitated the spread of this lineage throughout the world.